Lower Education and Reading and Writing Habits Are Associated With Poorer Oral Discourse Production in Typical Adults and Older Adults - Malcorra, Bárbara Luzia Covatti; Wilson, Maximiliano A.; Schilling, Lucas Porcello; Hübner, Lilian Cristine (Frontiers in Psychology, 2022)
This study aimed at investigating the effect of education and frequency of reading and writing habits (RWH) on oral discourse production during typical adults and older adults. Picture-based narratives were collected from 117 healthy adults, age between 51-82 years (68.6 ± 6.38) with 0-20 years of formal education (10.1 ± 5.69). Macro and microlinguistic measures, as well as modalizations, were quantified. Hierarchical regression analyses revealed that higher education explained the production of more macropropositions and better global coherence in the macrostructure level, and the production of more content-related complete propositions, ellipses, local coherence, and fewer incomplete propositions, fewer cohesive and cohesive information errors in the microstructure level. Higher frequency of RWH explained the production of fewer modalizations. These results demonstrate the positive effect of education on macro and microlinguistic aspects of oral discourse production in typical aging, as well as the positive effect of frequency of RWH on modalizations. Therefore, higher attention should be given to these social factors.